MENJAGA HUBUNGAN KELUARGA JARAK JAUH MELALUI NEW MEDIA (STUDI PADA ANGGOTA KELUARGA YANG TINGGAL BERBEDA KOTA) - Arnold Surya Nugroho (Jurnal Sosial Humaniora dan Pendidikan, 2022)
The research entitled "maintaining long-distance family relationships through new media (study of family members who live in different cities)", aims to find out how a family maintains good relations in order to be able to communicate effectively even though they live in different cities. This research was conducted in Jakarta and its surroundings. The problem in this research is how a family member uses new media or their smartphone to call their family or not. The research method used is descriptive, using field study data collection techniques and interviews. The number of informants interviewed was 5 people, the interview technique used by the author was unstructured interviews. The definition of unstructured interviews is a method used to obtain direct and in-depth information, in this case this technique is carried out without drafting questions, so that informants can express themselves (istijianto 2005). While the number of people who were observed was 2 people. From the results of research conducted by researchers in analyzing each answer given by each informant and found that they consider this family communication important and always provide news to each other. They use their smartphone technology to call them at every opportunity. The conclusion of the research is that the informants maintain their family communication for one important reason, namely if we don't maintain this family relationship, we don't know each other more closely. Whereas in this day and age they use new media technology or their smartphones to often call their families even though they are busy, they still call at every opportunity.